Balancing Work And Life: The Role Of Work Stress And Work-Life Balance On Employee Performance At The Pematang Siantar District Court - Ranti Resianna Uliarta Simanjuntak; Faisal Akbar; Muhammad Fahmi (Cita konsultindo, 2025)
This study seeks to examine the effects of workplace stress and work-life balance on employee performance at the Pematang Siantar District Court. Elevated work stress can adversely impact employee productivity, whereas a favorable work-life balance can improve performance and job satisfaction. This research utilized a quantitative methodology, employing census sampling to incorporate all 50 employees of the Pematang Siantar District Court as participants. Data were gathered via questionnaires and examined using multiple linear regression analysis. The results indicate that work stress adversely affects employee performance, while work-life balance positively influences it. Moreover, work-life balance is the predominant element influencing employee success. These findings underscore the significance of organizational policies in mitigating work stress and facilitating a balanced work-life dynamic to cultivate a healthier and more productive workplace.